Analisis Penerapan Community Based Tourism Pada Geosite Tebat Rasau, Kabupaten Belitung Timur - Danda Danda; Tuti Mutia (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
Tebat Rasau Geosite is one of the geosites within the Belitung Geopark, located in Lintang Village, East Belitung Regency, and is managed through the involvement of the local community. The area adopts the concept of Community-Based Tourism (CBT), a tourism development model that positions the community as the main actor. CBT includes five key aspects: economic, social, cultural, environmental, and political. This study was conducted due to the limited research exploring the comprehensive implementation of all five aspects of CBT at Tebat Rasau Geosite. The purpose of this research is to analyze the extent to which these aspects have been applied in the area. A qualitative descriptive method was employed, with data collected through interviews, direct observations, and document analysis. The findings indicate that the economic aspect is reflected in increased income and the creation of new jobs. The social aspect is demonstrated by the involvement of residents of various ages and the active role of women in tourism management. The cultural aspect is evident through the preservation of local traditions and cultural exchange with visitors. The environmental aspect is manifested in effective waste management and conservation activities. Meanwhile, the political aspect is shown through village regulations and government support that strengthen community roles. This study provides a comprehensive overview of how tourism can develop equitably and sustainably through active community participation.